2018
DOI: 10.1017/s1041610218000777
|View full text |Cite
|
Sign up to set email alerts
|

Delirium etiology subtypes and their effect on six-month function and cognition in older emergency department patients

Abstract: Delirium is heterogeneous and different etiologies may have different prognostic implications. Furthermore, the effect of these delirium etiologies on outcome may be dependent on the patient's pre-illness functional status and cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Precipitating factors for delirium span a wide range of different kinds of insults, including, amongst others, acute medical illness (such as sepsis, hypoglycaemia, stroke and liver failure), trauma (such as fractures or head injury), surgery, dehydration and psychological stress 17,27 . Typically, more than one precipitating factor is present in patients 50,51 . In addition, drug use and withdrawal and medication changes are associated with delirium.…”
Section: Prevalence Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitating factors for delirium span a wide range of different kinds of insults, including, amongst others, acute medical illness (such as sepsis, hypoglycaemia, stroke and liver failure), trauma (such as fractures or head injury), surgery, dehydration and psychological stress 17,27 . Typically, more than one precipitating factor is present in patients 50,51 . In addition, drug use and withdrawal and medication changes are associated with delirium.…”
Section: Prevalence Estimatesmentioning
confidence: 99%
“…Another study found that the duration of hypoactive delirium but not that of hyperactive delirium was associated with worse long-term cognitive function among critically ill patients experiencing delirium 303 . The potential influence of delirium aetiology, such as medications, infection or other causes, on outcomes has been explored in a small number of studies, with mixed findings 51,81 . However, these adverse outcomes all have a major role in a patient's QOL.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Frailty and delirium would appear to be two clinically distinct geriatric syndromes; however, their simultaneous onset has often been documented in the scientific literature [20, 24, 25]. Few studies have explored the associations between frailty and delirium on admission to Swiss ED [31, 32, 33, 34, 35]. Highlighting an association between frailty and delirium could lead to a better understanding of both these geriatric syndromes and their interdependence, to prevent and detect them more consequently in the ED [33, 35].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explored the associations between frailty and delirium on admission to Swiss ED [31, 32, 33, 34, 35]. Highlighting an association between frailty and delirium could lead to a better understanding of both these geriatric syndromes and their interdependence, to prevent and detect them more consequently in the ED [33, 35]. Nevertheless, few authors have sought to evidence any relationship between frailty and the initiation of other geriatric syndromes in the ED [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Another psychiatric condition encountered in cognitive disorders is delirium. [23,24] Prevalence of delirium, a clinical syndrome characterized by sudden-onset dysfunction of attention and cognitive function, is 11-16% among inpatients hospitalized due to physical illness with a more widespread distribution between 4-31%. [25] According to a systematic review of eight studies by Hosie et al, [26] 98.9% of inpatients receiving palliative care were cancer patients, delirium incidence was 3-35%, and delirium prevalence ranged between 13.3-42.3% at hospital admission.…”
Section: Discussionmentioning
confidence: 99%